Enterolitíase em equinos da raça crioula - Santos, Alice Correa; Curcio, Bruna da Rosa; Finger, Ilusca Sampaio; Júnior, Jarbas Castro; Nogueira, Carlos Eduardo Wayne (Acta Scientiae Veterinariae, 2017)
Enteroliths are intestinal mineral calculi predominantly composed of struvite. In horses this material accumulates concentrically around a core, causing total or partial obstruction of the higher and lower colon, and can lead to death by rupture. The enterolithiasis has worldwide distribution, and occurs frequently in Rio Grande do Sul, especially in Crioulo Horses. The aim of this work is to report a sequence of cases of Crioulo Horses with enterolithiasis, linking risk factors through historical analysis, clinical presentation and management employed by the breeding farms. Case: Between the years 2012 and 2015, 16 Crioulo Horses with colic syndrome caused by enteroliths were treated at the Hospital de Clínicas Veterinária of Universidade Federal de Pelotas (UFPel), RS, Brazil and Clínica Hípica, in Porto Alegre, RS. The group was formed predominantly by males, weighted 430 kg in average and the average age was eight years old. All horses underwent general and specific clinical examination, laboratory tests and surgical procedure to remove the enterolith. After discharge, there was an epidemiological questionnaire seeking information about the history, food and environmental management that could be related to the development of enterolithiasis. In relationship to the history of previous episodes of colic, the results were: 4 horses (25%) had no previous episodes of colic, while 12 horses (75%) had experienced previous colic. Regarding the horses’ bedding, 70% use sawdust and 30% rice husk, and about behavior, ten (62.5%) of the 16 horses attended had no stereotypies. Related to food and water supply, it was observed that nine horses (56.25%) had alfalfa as the only roughage source in the diet, and all animals (100%) were fed commercial food and water ad libitum. According to the number of hours the patients remained stabled, the rearing system was classified as intensive (over 12 h/stable/day), extensive (0 h, at the field) or semi-extensive (up to 12 h/stable/day). The frequencies observed were: intensive (9 animals - 56.25%), semi-intensive (6 animals - 37.5%) and extensive (1 animal - 6.25%). The average time of stabling was 17.2 h/day. Discussion: The alfalfa consumption as the only forage observed in our study is the main risk factor described for the formation of enteroliths. This is because in digestion, alfalfa tends to alkalize the intestinal pH, hindering the metabolism of some minerals and thus forming the enterolith. Another important risk factor observed in this work is the intensive rearing, with long periods of stabling. This explains why confinement leads to decreased intestinal motility, due to reduced or absent grazing. Furthermore, reduced physical activity is another contributing factor to the reduction of motility, because the exercise influence the intestinal peristalsis. The rearing of horses intensively is usual with the Crioulo, especially in training and morphological preparation. Based on this case study, we can’t say that there is a racial predisposition to enterolithiasis of the Crioulo Horse, since it would require more studies on the physiology and a standard feeding of these horses. However, we can attribute the considerable volume of enteroliths observed in Crioulo Horses in Rio Grande do Sul to the increase in the number of referrals to the reference hospitals, feeding alfalfa as the only roughage source in the diet and to intensive management of the farms, with long periods of daily stabling.